PROLIFERASI NUKLIR SEBAGAI PENCIPTA PERDAMAIAN DUNIA KONTEMPORER: SEBUAH TINJAUAN LITERATUR - Febry Triantama (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
Nuclear weapons are a form of weapon technology developed that have enormous power. With just a small amount, nuclear weapons can destroy a city through its explosive power and the radiation it emits. The presence of nuclear weapons with all the strength they have and the desire of several countries to develops their nuclear weapons made a debate in International Relations realms. The first opinion states that nuclear proliferation will threaten world stability or peace. Meanwhile, the second opinion is a nuclear proliferation will bring a more peaceful international system. This debate continues today. Through a literature study approach, this article states that the opinion that states nuclear proliferation helps create a more stable and peaceful international world is more relevant to contemporary international politics.